Perkembangan Perekonomian Dan Mata Pencaharian Masyarakat Arab Dari Pra-Islam Hingga Datangnya Islam - Wisnu Fachrudin Sumarno; Ahmad Sodikin; Dony Rano Virdaus (Program Studi Sejarah Peradaban Islam Institut Agama Islam Darullughah Wadda'wah, 2025)
The Arab nation is broadly divided into two parts, namely the population living in villages and the population living in cities. The livelihood of the rural population is mostly livestock, while the livelihood of the city dwellers is trading in the market. This study aims to explore the various livelihoods of Arab society from the pre-Islamic era to the arrival of Islam. This study is a literature review with a sociological approach and uses historical research methods with four main stages in techniques and data analysis. The four stages are heuristics for data collection, verification to assess the validity of sources, interpretation to analyze the meaning of data, and historiography to compile research results narratively. The results of this study indicate that the livelihoods of pre-Islamic Arab society are divided into two, namely rural communities (Bedouin) and urban communities. In the Badui community they hunt for daily food needs besides that they also farm, while for urban communities the work done is trading after the arrival of Islam the work of the community is still the same plus carpentry, and mining during the time of the Prophet to Khulafa al rasyidin and modern work is becoming a translator, writer, soldier and state administration during the Islamic dynasties.